RETURN MIGRATIONS IN SPAIN UNDER FRANCO: POLICIES, PERCEPTIONS AND DISCOURSES, 1939-1975 (Estudios de Historia de España, 2022)
The policies, perceptions and discourses around return migration to Spain during the years of Franco dictatorship were transformed in parallel to the changes experienced by emigration outside the country. This article analyses this transformation of return migration, initially identified with repatriation, until its conceptualization within the framework of assisted migration schemes articulated in the Europe of the “guestworker system”. This transformation took place as a result of the displacement of the American migration cycle by the European migration cycle. In this process, return migration lost its assistance character and began to be conceived from an economic and labor perspective that connected with de developmental objectives of the Spanish government. Based on archival research and the analysis of legislative texts, publications and cultural production, this essay highlights the limits and contradictions of the discourses and public policies on return migration under the dictatorship.
Keywords: Migration; Return Migration; Francoism; Politics; Discourses.